(untitled) (Dhaka University Journal of Biological Sciences, 2015)
In an average, 6648 fungal colony forming units were settled within five minutes on one square meter area at morning and evening from the air of Dhaka Metropolitan city during February, 2013 to January, 2014. Among the identified fungi, Aspergillus was one of the most dominating genera in all the stations during the above mentioned period. The second was Cladosporium followed by Penicillium, Alternaria, Curvularia, Fusarium, Pestalotia, Colletotrichum, Tricho‐derma, Rhizopus, Nigrospora, Chaetomium, Syncephalastrum, Arthrinium and Bipolaris. In the dry winter (December‐February), Alternaria, Bipolaris, Cladosporium, Curvularia and Drechslera showed its peak. In the rainy monsoon (June ‐ September), Aspergillus, Fusarium, Penicillium, Pestalotia and Trichoderma showed their peak. Dhaka Univ. J. Biol. Sci. 24(1): 25-33, 2015 (January)